Perceptions Of Residents Of The Hosting Of The "Guimar\~aes 2012 European Capital Of Culture": An 'Ex-Ante' Aproach - Paula Remoaldo; Mécia Mota; José Cadima Ribeiro (European Regional Science Association (ERSA), 2013)
In a context of economic crisis, is culture doomed to have a minor role in public policies or, by the contrary, is it able to contribute to the creation of employment and income, thereby, justifying the huge investment made by cities in hosting mega events such as the European Capitals of Culture? The European Capital of Culture is an annual mega event, which can be a good way of challenging and engaging local citizens, generating feelings of common citizenship. Besides, it is an ideal opportunity to promote the restructuring of the hosting urban space. However, the success of, both, the organization and the city that hosts the cultural event depend on the commitment of residents towards it, and of the consistency of the supply of tourism attractions and activities and of the capacity of anticipating and monitoring the evolution of the tourists' preferences. The present study aimed to assess the impacts perceived by residents of Guimar\~aes (northwest of Portugal) of the hosting city of the 2012 European Capital of Culture (2012 ECOC) in the ex-ante period (the year of 2011). Through a convenience sample of 510 surveys applied to the local population, complemented by semi-structured interviews to local and regional actors, conducted between October and December 2011, we tried to identify some of these potential impacts. In order to create the sample, we contacted the municipality?s four public secondary schools and one professional school. This allowed us to almost cover the 69 parishes which constitute the municipality of Guimar\~aes. By targeting the high schools, we were able to consider three generations of inhabitants (15?24-year-olds, 25?64-year-olds and the 65 or more years old residents) in our survey. According to the results, only 42.4% of residents had a reasonable prior knowledge of the mega event and, with regard to participation, only 14.9% intended to participate.
Keywords: L83; 330; European Capital of Culture; 2012 ECOC; Residents perceptions; Megaevents impacts; Guimar\~aes